Global, regional and national burdens of non-melanoma skin cancer attributable to occupational exposure to solar ultraviolet radiation for 183 countries, 2000–2019 - Pega, Frank (2023)
Funding Information: Countries provided feedback on the estimates through WHO's consultation of its 194 Member States. We specially acknowledge the ILO for its strategic contributions, as well as its sharing of data and contributions to the production of the estimates. Eurostat produced and shared the transition probabilities for exposure to UVR assigned via proxy of occupation for 27 countries in the European Region. Dr Yuka Ujita (ILO) and then Dr Halim Hamzaoui (ILO) were the ILO focal point for the WHO/ILO Joint Estimates. Marion McFeedy (consultant to the ILO) contributed to initial database development, and Dr Bochen Cao (WHO) shared WHO Global Health Estimates. Dr Claudine Backes (WHO) and Dr Emilie van Deventer (WHO) contributed to the early development of the estimation approach. Jessica CY Ho (WHO), Wahyu R Mahanani (WHO), Dr Bálint Náfrádi (ILO), Dr Annette M Prüss (WHO) and Dr Yuka Ujita provided feedback on an earlier version of the manuscript. Dr Ivan D Ivanov (WHO), Nancy Leppink (ILO), Franklin Muchiri (ILO), Dr Maria P Neira (WHO), Vera L Isaac Paquete-Perdigão (ILO) and Joaquim P Pintado Nunes (ILO) contributed to the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury. Dr Maria P Neira and Vera L Isaac Paquete-Perdigão provided overall guidance. Funding Information: This modelling study was prepared with financial support to WHO from: the National Institute for Occupational Safety and Health of the Centers for Disease Control and Prevention of the United States of America (Grant 1E11OH0010676-02, Grant 6NE11OH010461-02-01 and Grant 5NE11OH010461-03-00); the German Federal Ministry of Health (BMG Germany) under the BMG-WHO Collaboration Programme 2020–2023 (WHO specified award ref. 70672); and the Spanish Agency for International Cooperation (AECID) (WHO specified award ref. 71208). The funders had no role in study design, data collection and analysis, decision to publish or preparation of the manuscript. Publisher Copyright: © 2023 International Labour Organization, World Health Organization